2000
DOI: 10.1515/cclm.2000.061
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Lp(a) and other Apolipoproteins in Predialysis, Hemodialysis, Chronic Ambulatory Peritoneal Dialysis and Post-Transplant Patients

Abstract: Serum levels of lipids, lipoprotein(a) Lp(a) and other apolipoproteins were determined in 47 predialysis patients, 40 hemodialysis (HD) patients, 39 chronic ambulatory peritoneal dialysis (CAPD) patients, 11 patients after kidney transplantation and 47 healthy subjects as reference group. The predialysis, HD, and CAPD patients had disturbances in the concentration of serum triglyceride (TG), high density lipoprotein (HDL)-cholesterol, apolipoprotein AI (apoAI), total apoCIII, apoCIII present in the particles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Previous study showed that abnormal concentrations of Lp(a) in patients with endstage renal disease might be the cause of the high risk of atherosclerosis. 19 In this study, the serum levels of Lp(a) were significantly higher in overweight patients, which may be related to high cardiovascular disease, therefore contributed to increased mortality in overweight patients. The research also showed that serum levels of CRP were significantly higher in overweight patients than in normal weight patients, which was in accord with the results from de Araujo Antunes et al 20 At the same time, linear regression analysis found that CRP was a significant risk factor associated with BMI.…”
Section: Resultsmentioning
confidence: 57%
“…Previous study showed that abnormal concentrations of Lp(a) in patients with endstage renal disease might be the cause of the high risk of atherosclerosis. 19 In this study, the serum levels of Lp(a) were significantly higher in overweight patients, which may be related to high cardiovascular disease, therefore contributed to increased mortality in overweight patients. The research also showed that serum levels of CRP were significantly higher in overweight patients than in normal weight patients, which was in accord with the results from de Araujo Antunes et al 20 At the same time, linear regression analysis found that CRP was a significant risk factor associated with BMI.…”
Section: Resultsmentioning
confidence: 57%
“…It has also been shown that patients treated with PD have higher levels of serum triglycerides, total cholesterol, LDL, and lower levels of high-density lipoproteins compared with HD-treated patients (12)(13)(14). Furthermore, comparisons of PD and HD patients have found greater increases in lipoprotein (a) levels in those treated with PD (12). Such evidence points to PD as being more proatherogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that certain cardiovascular conditions, including fatal stroke and left ventricular hypertrophy occur with greater frequency in patients treated with PD compared with HD (36 -39). It has also been shown that patients treated with PD have higher levels of serum triglycerides, total cholesterol, LDL, and lower levels of high-density lipoproteins compared with HD-treated patients (12)(13)(14). Furthermore, comparisons of PD and HD patients have found greater increases in lipoprotein (a) levels in those treated with PD (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reasons for the higher mortality of patients treated with PD were proposed. First, the serum lipoprotein (a) (Kimak et al 2000;Kronenberg et al 2003) and hyperlipidemia (Lee et al 1998;Kronenberg et al 2003) levels are reported to be higher in patients undergoing PD than in patients undergoing HD. Accelerated atherosclerosis may occur in the PD patients.…”
Section: Discussionmentioning
confidence: 99%